Intersections of gender and class in the distribution of income. Issue 1 (2nd October 2018) - Elson, Diane
Abstract: This article considers the intersection of gender and class in the distribution of income. The first section applies a gender lens to reread Piketty's Capital in the Twenty-First Century, showing how the analysis would be different if capitalism were recognized as not only patrimonial but also patriarchal. The second section discusses an OECD study that claimed, "More women in paid work means less income inequality, " taking into account unpaid work as well as paid work. The third section discusses the claim that rising female labor force participation is associated with a rise in inequality between capital and labor. The final section considers strategies to reduce both gender inequality and class inequality.